Utilisation of coaching practices in early interventions in children at risk of developmental disability/delay: a systematic review. Issue 20 (24th September 2020) - Ward, Roslyn; Reynolds, Jess E.; Pieterse, Bridget; Elliott, Catherine; Boyd, Roslyn; Miller, Laura
Abstract: Background: To conduct a systematic review of early intervention programs (0–5 years) utilising coaching practice characteristics, to identify (i) implementation fidelity; (ii) parent training processes, and (iii) outcome measures of capacity building in parents. The coaching practice characteristics of (1) joint planning, (2) observation, (3) action/practice, (4) reflection and (5) feedback identified by Rush and Shelden were utilised. Method: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement was followed. A comprehensive search of 6 electronic databases was undertaken in March 2016 and updated in February 2018. Results: Of 2397 articles, 18 papers met full inclusion criteria. Of these, 5 were randomised controlled trials. Only one specifically evaluated the impact of parent coaching versus therapist only delivered interventions. Risk of bias and study quality using Downs and Black checklist for clinical trial quality yielded the following descriptive ratings: Seven studies: "Poor" (scores 1–13); Six studies: "Fair" (scores 15–17); and five "Good" (scores 20–24). Conclusion: Coaching in early intervention is well accepted. Nevertheless, this review identified a continued lack of operationalised definitions; inconsistency in the reporting of therapist training and adherence to active ingredients/coaching principles; and an absence of outcome measures focused on parent capacity. Implications for Rehabilitation: Contemporary early intervention services recognise the importance of engaging parents as active participators in their child's development. This is evident by the increase in interventions that utilise parent coaching practices. The findings of this systematic review indicate the need for professionals to: Describe and document fidelity of coaching practices in the delivery of intervention. Objectively measure changes in parent capacity and self-efficacy as a result of the coaching based intervention. The reporting of parent capacity measures will allow us to truly examine the effectiveness of coaching practices in empowering families to support their child to realise their full potential.